Glucose regulates heat shock factor 1 transcription activity via mTOR pathway in HCC cell lines. (6th July 2015) - Ma, Wanli; Zhang, Yaqing; Mu, Hongmei; Qing, Xiaoming; Li, Shulian; Cui, Xiukun; Lou, Qiang; Ma, Yuanfang; Pu, Hongmin; Hu, Yanzhong
Abstract HSF1‐mediated heat shock response is activated in most tumors and plays important roles in regulating tumor homeostasis. However, the signals underlying HSF1 activation is still not completely understood. In this paper, we find that glucose, the dominant tumor energy supplement, participates in regulating HSF1's activation in HCC cell lines. The immunoblotting results indicate that the phosphorylation of HSF1/S326, a hallmark of HSF1 activation, varies between the HCC cell lines (e.g., SMMC7721, HapG2, plc/prf5, and Chang‐liver). Glucose, but not 2D‐glucose, can induce the phosphorylation of HSF1 at S326 and upregulate the expression of HSF1's downstream alpha B‐crystallin and Hsp70 as well as the none‐heat shock proteins CSK2 and RBM23 in two tested hepatocellular carcinoma cell lines (prl/prf5 and SMMC7721). Rapamycin, an inhibitor of mTOR, can suppress the glucose‐induced phosphorylation of HSF1/S326 and the expression of alpha B‐crystallin. Knockdown of HSF1 with shRNA enhances the glucose‐depletion‐mediated inhibition of plc/prf5 cell proliferation. Our data reveal that HSF1 can be activated by glucose‐mTOR pathway, providing an alternative pathway for targeting HSF1 in tumor therapy.